GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN SUMBER DAYA MANUSIA DI TK DHARMA INDRIA II - Ayu Tri Agustin; Octavian Dwi Tanto; Yuli Tri Andini; Aisyah Nur Atika; Muchammad Arif Muchlisin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT the availability of training opportunities, but also the ways in which principals guide, involve, and place trust in teachers throughout their professional development. Studies on principal leadership and teacher human resource development are still frequently treated as separate areas, even though both intersect in the day-to-day management of educational institutions. This study describes principals’ leadership styles in developing teachers’ human resources across the stages of planning, implementation, monitoring, and evaluation at Dharma Indria II Kindergarten. A descriptive qualitative approach was employed, involving one principal, five teachers, and one administrative staff member selected through purposive sampling. Data were collected through participant observation, semi-structured interviews, and documentation, then organized through thematic coding and narrative interpretation. The credibility of the findings was strengthened through source, technique, and theoretical triangulation. The principal’s leadership emerged as an adaptive practice that combined direct decision-making when competency needs required immediate attention, deliberation when development agendas were formulated, and the provision of professional autonomy when teachers implemented training outcomes in their classroom practices. These three orientations authoritarian, democratic, and laissez-faire operated situationally rather than as isolated leadership patterns. The findings suggest that teacher human resource development becomes more meaningful when training facilitation is connected to needs assessment, dialogic supervision, and reflection on the application of learning outcomes in classroom practice. ABSTRAK tersedianya pelatihan, tetapi juga dengan cara kepala sekolah mengarahkan, melibatkan, dan memberi kepercayaan kepada guru dalam proses profesionalnya. Kajian mengenai kepemimpinan kepala sekolah dan pengembangan SDM guru masih sering dipisahkan, padahal keduanya bertemu dalam praktik pengelolaan lembaga sehari-hari. Penelitian ini mendeskripsikan gaya kepemimpinan kepala sekolah dalam pengembangan SDM guru pada tahap perencanaan, pelaksanaan, monitoring, dan evaluasi di TK Dharma Indria II. Penelitian menggunakan pendekatan kualitatif deskriptif dengan melibatkan satu kepala sekolah, lima guru, dan satu tenaga kependidikan yang dipilih secara purposive. Data diperoleh melalui observasi partisipatif, wawancara semi-terstruktur, dan dokumentasi selama proses penelitian, lalu ditata melalui pengodean tematik dan interpretasi naratif. Kredibilitas temuan diperkuat melalui triangulasi sumber, teknik, dan teori. Kepemimpinan kepala sekolah tampak sebagai praktik adaptif yang memadukan keputusan langsung ketika kebutuhan kompetensi harus segera ditangani, musyawarah ketika agenda pengembangan dirumuskan, serta pemberian otonomi profesional ketika guru menerapkan hasil pelatihan dalam pembelajaran. Ketiga corak tersebut otoriter, demokratis, dan laissez-faire berfungsi secara situasional, bukan sebagai pola yang berdiri sendiri. Temuan ini menunjukkan bahwa pengembangan SDM guru lebih bermakna ketika fasilitasi pelatihan dihubungkan dengan pemetaan kebutuhan, supervisi dialogis, dan refleksi atas penerapan hasil belajar di kelas.